How does language play a role in intercultural communication today? Chapter review of intercultural communication in contexts, 8th edition by Judith N. Martin and Thomas K. Nakayama - Ayu Muhammad, Anugrah Puspita; Asbar, Asbar; Samsuddin, Samsuddin; Misnawati, Misnawati (Journal for Teaching and Education for Scholars, 2022)
This article is a review chapter of Judith N. Martin and Thomas K. Nakayama's book entitled "Intercultural Communication in Contexts, 8th Edition. The chapter reviewed in this article is Chapter 6 with the sub-title Language and Intercultural Communication. This chapter focuses on discussing issues - issues related to language in the process of verbal communication. In this article, the authors also present the cultural variations of language and some of the barriers that these variations pose, the relationship between language and power, and between language and identity, and examine multilingualism, translation, and interpretation issues. So in this paper, as a review chapter, we look at language and identity, language rules and politics, and globalization.